Perancangan Strategi Bisnis Menggunakan Business Model Canvas Analisis SWOT dan Analytical Hierarchy Process Pada UMKM Lestari Kopi - Aulawi, Hilmi; Taptajani, Dedi Sa'dudin; Faujani, Zidan Ahmad (Jurnal Kalibrasi, 2024)
This research aims to find out the description of the business model of Sustainable Coffee MSMEs in terms of the company's BMC and to find out the company's strategy using SWOT and AHP analysis which can be developed based on the BMC results and then design the business model that will be implemented by Sustainable Coffee MSMEs which is described in BMC future. The approach used, namely descriptive qualitative with Business Model Canvas analysis techniques and SWOT Analysis. The respondents in this research were three respondents who have an important role in Sustainable Coffee MSMEs. The results of this research are improvements to the current Business Model Canvas mapping which includes nine elements, namely customer segment, value proposition, customer relationship, channel, revenue stream, key partnership, key activity, key resource, cost structure and the results of the SWOT analysis regarding design business development strategy from the Business Model Canvas. The results of the SWOT analysis provide an overview of the company's condition in quadrant III (WO). Three strategies were obtained from the SWOT (WO) matrix, then weighted using the Analytical Hierarchy Process (AHP) to determine which strategy had the highest priority based on expert views. Data processing using expert choice 11 software obtained the WO3 strategy which was used as an alternative company business strategy. Formulated proposals regarding innovation and additional product varieties of subsidiary companies.